Digital storytelling with Acehnese cultural values: A pathway to developing English writing competence - Syuja, Sarair; Trisnawati, Ika Kana; Yuniarti, Yuniarti; Taufik, Taufik (Englisia Journal, 2025)
Proficiency in English academic writing is a critical competency for university students; however, pedagogical approaches often lack cultural relevance, which can impede engagement and skill development. This study investigated the efficacy of Digital Storytelling (DST) grounded in Acehnese local wisdom as a means to enhance students’ writing skills and reinforce their cultural identity. The pedagogical intervention explicitly encouraged students to integrate traditional Acehnese cultural elements, such as Meugang and Peusijuk, into their English compositions, thereby forging a meaningful connection between language acquisition and cultural heritage. Employing a quasi-experimental design, the research involved a purposive sample of 20 English major students from universities across Aceh. Writing proficiency was measured via pre-test and post-test assessments, while a supplementary questionnaire captured students’ perceptions of the DST methodology. Data were analyzed using SPSS software, applying both descriptive and inferential statistics. A Wilcoxon signed-rank test indicated a statistically significant improvement in overall writing performance, confirming the intervention's effectiveness. Findings demonstrate that students successfully incorporated Acehnese cultural narratives into their writing and reported heightened motivation, engagement, and enjoyment throughout the process. Specific gains were noted in vocabulary expansion, narrative idea generation, and confidence in English self-expression. However, development in technical aspects of writing—such as text organization and coherence—was only moderate, suggesting that DST may be more effective for stimulating cultural engagement and creative expression than for mastering formal writing conventions. These results underline the value of culturally responsive pedagogies in second language writing instruction.